115 Lethal trisomies: a 15-year review in a paediatric tertiary centre. (15th December 2021) - Billington, Jennifer; Costigan, Fiona; Criag, Finella; Curry, Joe; Cross, Kate; DeCoppi, Paolo
Abstract : Background: A lethal chromosomal anomaly is defined as a congenital condition leading to a shortened lifespan. T18(Edward's syndrome) and T13(Patau's syndrome) are described as lethal with a median survival of 14 days for T18 and 10 days for T13.The incidence of T18and T13 is 1/8000 and 1/5000 respectively. Both conditions can be full, mosaic or partial chromosomal anomalies and are associated with a wide spectrum of congenital defects. Many patients require medical and surgical procedures. Methods: Following study registration, a retrospective review of Electronic Patient Record (EPR) database was performed. Over a 15-year period from 2006 – 2021, those with a coded lethal trisomy (13 or 18) were included. Patient demographics were recorded, along with the presence of congenital cardiac disease and need for surgical intervention. Results: 87 patients were identified in our analysis, 31(36%) male and 60(68%) with trisomy 13. 44(51%) babies had congenital cardiac disease, with 26 patients having a VSD diagnosis... 46(53%) were referred for surgical intervention.6/46(13%) were deemed unfit for surgery due to cardiac disease. General surgical procedures were carried out most frequently in 24/40 (60%), and Nissen's fundoplication was the most common procedure. No baby died as a direct complication of surgery.50/87(57%) of patients were alive at the time of this review. The overall median age of death was 331 days. In those with and without congenital cardiac disease, the median age of death was 11.65 and 192 days respectively. The median age of death in patients undergoing surgical procedure was 5.94 years compared to 67 days who did not. Discussion: This study is the largest cohort of patients with a lethal trisomy in published literature. Whilst the literature would suggest the prognosis for long term survival in children with T13 and T18 is uniformly poor, our study would suggest survival is better than once thought, particularly in those without congenital cardiac disease and/or eligible for surgical intervention.